The Retrieved Altar Cross of the Luther Church Helsinki : Sacred Waste Transformed into a Heritagization Frame - Dahlbacka, Jakob (Approaching Religion, 2024)
The topic of this article is religious materiality in a Finnish, Lutheran setting. Reflecting on the altar cross of the Luther Church Helsinki – and more specifically the elevated role the cross played in the re-opening of the church in 2016 – the article supports the argument of recent scholars that Protestant engagement with materiality is not unambiguously negative but rather ambivalent. Using James Bielo’s concept of “legitimizing frames” – i.e. boundaries or landmarks within which Protestants feel safe enough to deal with things and objects – the article suggests a so-called heritagization frame. Objects or things used within such a frame induce in people a sense of past events and experiences – preferably events in which God has made himself known in this world. This, in turn, enables people’s engagement with the objects.